Red alert: disinformation, post-truth and fake news a constant threat to society (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
Terms such as disinformation, fake news, and post-truth have become increasingly common in society's daily life. So how has the production of Information Science contributed to the identification, analysis, and combat of disinformation and fake news in contemporary society? Thus, Information Science, which investigates the production, dissemination, and other information flows, has started to pay more attention to these topics, especially after the presidential elections in Brazil. This study aimed to map the publications in the Database in Information Science (Bracip), using the terms fake news, disinformation, and Information Science for the period from 2022 to 2023. A total of 33 articles were found, which were categorized after reading the abstracts. The results show that the majority of the studies focus on combating disinformation, addressing themes such as information literacy, critical information competence, and mediation, among others.
Keywords: disinformation; post-truth; Fake news; information literacy